Foreign Guests in Ancient Greece - Zora Žbontar (Ars & Humanitas, 2013)
Xenía was a special relationship between a foreign guest and his host in Ancient Greece. The ritual of hosting a foreigner included an exchange of objects, feasting, and the establishment of friendship between people from different social backgrounds. This relationship implied trust, loyalty, friendship, and mutual aid between the people involved. Goods and services were also exchanged without any form of payment. There were no formal laws governing xenía – it was based entirely on a moral appeal. Mutual appreciation between the host and the guest was established during the ritual, but the host did retain a certain level of superiority over the guest. Xenía was one of the most important institutions in Ancient Greece. It had a lot of features and obligations similar to kinship and marriage. In literary sources the word xénos varies in meaning from “enemy stranger”, “friendly stranger”, “foreigner”, “guest”, “host” to “ritual friend”, and it is often hard to tell which usage is appropriate in a given passage. The paper describes the emphasis on hospitality towards foreigners. It presents an example of a depiction indicating xenía is presented, as well as several objects which were traded during the ritual. The paper also addresses the importance of hospitality in Greek drama in general, especially with examples of violations of the hospitality code.